2011
DOI: 10.4152/pea.201102127
|View full text |Cite
|
Sign up to set email alerts
|

Fennel (Foeniculum Vulgare) Essential Oil as Green Corrosion Inhibitor of Carbon Steel in Hydrochloric Acid Solution

Abstract: Essential oil from fennel (Foeniculum vulgare) (FM) was tested as corrosion inhibitor of carbon steel in 1 M HCl using electrochemical impedance spectroscopy (EIS), Tafel polarisation methods and weight loss measurements. The results show that the increase of the charge-transfer resistance (R ct ) with the oil concentration supports the molecules of oil adsorption on the metallic surface. The polarization plots reveal that the addition of natural oil shifts the cathodic and anodic branches towards lower curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Plant extracts have become important as an environmentally acceptable readily available and renewable source for a wide range of corrosion inhibitors 9 . Plant extracts are viewed as an incredibly rich source of naturally 12 , Hibiscus sabdariffa extract 13 , Clematis gouriana 14 , Aloe vera extract 15 , Phyllantus amarus extracts 16 , Dacroydes edulis 17 , Murraya koenigii 18 , Foeniculum vulgare 19 , Chlomolaena odorata L 20 , Radish 21 and Jasminum nudiflorum 22 have been reported as effective corrosion inhibitors for metals in acidic, alkaline and neutral solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts have become important as an environmentally acceptable readily available and renewable source for a wide range of corrosion inhibitors 9 . Plant extracts are viewed as an incredibly rich source of naturally 12 , Hibiscus sabdariffa extract 13 , Clematis gouriana 14 , Aloe vera extract 15 , Phyllantus amarus extracts 16 , Dacroydes edulis 17 , Murraya koenigii 18 , Foeniculum vulgare 19 , Chlomolaena odorata L 20 , Radish 21 and Jasminum nudiflorum 22 have been reported as effective corrosion inhibitors for metals in acidic, alkaline and neutral solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The plant extracts are viewed as an incredibly rich source of naturally synthesized chemical compounds that can be extracted by simple procedures with low cost, and are biodegradable in nature [8]. Recently, several natural compounds such as, Azadirachta indica [9], Isertia coccinea [10], Prosopis cineraria [11], Hibiscus sabdariffa extracts [12], Clematis gouriana [13], Aloe vera extracts [14], Phyllantus amarus extracts [15], Dacroydes edulis [16], Murraya koenigii [17], Foeniculum vulgare [18], Chlomolaena odorata L. [19], Radish and black cumin [20], Jasminum nudiflorum [21] and Bridelia retusa leaves extract [22] have been reported as effective corrosion inhibitors for metals in acidic, alkaline and neutral solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The Nyquist plots of mild steel at the various concentrations of sarang semut extracts in the inhibitor exhibited a similar pattern. This indicates that the inhibition mechanism (a chargetransfer process between the inhibitor and the metal surface) was also similar (Al-Otaibi et al, 2012;Lahhit et al, 2011). From the Nyquist plot, it is clear that the size of the capacitive loop increased with the increasing concentration of sarang semut extract.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Measurementmentioning
confidence: 64%
“…Santana reported that the first organic inhibitor in the pickling process using sulfuric acid was extract of Chelidonium majus (celandine) (Al-Otaibi et al, 2012). Uncaria gambir (Hussin & Kassim, 2011), Justicia gendarussa (Satapathy et al, 2009), green Capsicum annuum fruit (Ji et al, 2012), Murraya koenigii (Quraishi et al, 2010), Salvia officinalis (Soltani et al, 2012), and fennel (Foeniculum vulgare) (Lahhit et al, 2011) have also been reported as corrosion inhibitors (Santana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%